1987
DOI: 10.1002/nur.4770100604
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with health care of hemodialysis patients

Abstract: The purpose of this study was to assess the satisfaction with care of hemodialysis patients, and to explore the relationships between satisfaction with care, quality of life, and background variables. The sample (n = 416) was randomly selected from the adult, in-unit hemodialysis patient population of a north central state. Overall, patients were satisfied with their care (M = 5.04, range = 1 to 6). An ANOVA demonstrated that patients were most satisfied with physician related aspects of care, followed by nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 15 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…Internationally, studies have investigated satisfaction with services among patients on dialysis, but often focused on one type of dialysis or on comparing PD with HD 12–18 . Satisfaction with health professionals has been found to affect adherence to treatment and follow‐up 19 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Internationally, studies have investigated satisfaction with services among patients on dialysis, but often focused on one type of dialysis or on comparing PD with HD 12–18 . Satisfaction with health professionals has been found to affect adherence to treatment and follow‐up 19 .…”
mentioning
confidence: 99%
“…11 Internationally, studies have investigated satisfaction with services among patients on dialysis, but often focused on one type of dialysis or on comparing PD with HD. [12][13][14][15][16][17][18] Satisfaction with health professionals has been found to affect adherence to treatment and follow-up. 19 Information about satisfaction with dialysis services among older patients has the potential to inform the decision-making process and improve services to better meet the needs of patients and their families.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Since the inception of home TPN in the 1970s, quality of life has been studied from the individual patient's perspective and from an illness/condition perspective. 17-28…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Since the inception of home TPN in the 1970s, quality of life has been studied from the individual patient's perspective and from an illness/condition perspective. [17][18][19][20][21][22][23][24][25][26][27][28] Problems of depression and health or functional changes in both the patient and spouse have been identified.…”
mentioning
confidence: 99%
“…Specifically, participants were mostly satisfied with the nursing care they received, including the nurses' understanding of personal needs and concerns, nurses' management of emergencies, and nurses' time spent talking to patients. This study revealed that interpersonal relationships with nursing professionals were valued as highly as the medical and technological care these patients received (9). This finding is extremely important, because it demonstrates that nursing care is an important factor, which contributes to maintaining and improving patients' QOL.…”
Section: Quality Of Life Research: a Valuable Tool For Nephrology Nursesmentioning
confidence: 77%